2022
DOI: 10.1038/s41467-022-32806-y
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal dynamics of self-organized branching in pancreas-derived organoids

Abstract: The development dynamics and self-organization of glandular branched epithelia is of utmost importance for our understanding of diverse processes ranging from normal tissue growth to the growth of cancerous tissues. Using single primary murine pancreatic ductal adenocarcinoma (PDAC) cells embedded in a collagen matrix and adapted media supplementation, we generate organoids that self-organize into highly branched structures displaying a seamless lumen connecting terminal end buds, replicating in vivo PDAC arch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 49 publications
0
22
0
Order By: Relevance
“…Of note, the latter probably differ in various cell types, as glycosylation patterns are dynamic and also cell type-specific [ 63 ]. The characterization of glycosylated TFF2 receptors might open, also, new therapeutic options as well as allow the growth of functional pancreas-derived 3D organoids [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of note, the latter probably differ in various cell types, as glycosylation patterns are dynamic and also cell type-specific [ 63 ]. The characterization of glycosylated TFF2 receptors might open, also, new therapeutic options as well as allow the growth of functional pancreas-derived 3D organoids [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…From X-ray tomography, these cells surround the lumen within the retinal organoid and resemble the retinal pigmented epithelial layer seen in medaka embryos (Figure 5C and Supplementary figure 9). Several studies have suggested that lumen plays an active part in tissue morphogenesis (Randriamanantsoa et al 2022; Tallapragada et al 2021; Mukenhirn et al 2023). The complex spatial organisation of the lumen in the fish retinal organoid is clearly visible in the X-ray tomography data (Figure 5D).…”
Section: Resultsmentioning
confidence: 99%
“…The geometrical and morphological features of a tissue can affect the cell functionality and therefore represent another crucial aspect to consider in the design of a biomimetic model 41,76 . Although different engineering strategies have been adopted to obtain tubular lumen structures [41][42][43]73,77 , they lack in fully creating the 3D acinar-and ductal-like geometry 42,73 or in incorporating the stromal component 43,78 . However, our model currently replicates the glandular structure with 5:1 rescaled dimensions as compared to the physiological human gland (diameter of acinar portion 200 µm, of duct portion 50 µm).…”
Section: Discussionmentioning
confidence: 99%
“…This ratio is comparable or smaller than that of other models replicating the morphology of the pancreactic gland, including a hollow duct 43 . Additional work should be performed to enhance the resolution of the printed cavity, to make it more anatomically relevant 78 . In this context, the methodology applied to produce the in vitro model allows for a highly versatile approch, therefore, this model could be further improved by incorporating other cells involved in pathology development.…”
Section: Discussionmentioning
confidence: 99%